2016
DOI: 10.5433/1679-0359.2016v37n3p1229
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and biochemical changes induced by lead in sunflower (Helianthus annuus L.)

Abstract: The aim of this study was to evaluate the effects of increasing concentrations of lead (Pb) in the nutrient solution on growth and macronutrient and organic solute contents of Helianthus annuus plants. The experimental design was completely randomized with four replications. The dry mass yield was not affected by the treatments up to a Pb concentration of 0.6 mM, indicating that H. annuus was tolerant to this Pb concentration in the growth medium. The reductions in leaf, stem and root dry masses at a Pb concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…In the treatments analyzed, no significant differences were found in the leaves in terms of total protein content, but in the stem the highest concentration (100 mg kg -1 ) was significantly higher than the control in 135.1% and that the treatment with 50 mg kg -1 of PbAc 2 (136.59%), causing a significant decrease in the variable analyzed in both treatments (0 and 50 mg kg -1 of PbAc 2 ) (Figure 4A & 4B). This increase in the content of total soluble proteins in the maximum concentration of PbAc 2 used could be due to a saturation in the mechanisms of retention of Pb in the stem, and consequently the finite capacity of this organ to act as a reservoir of the metal, 14 which continues to the leaves, where, although without significant differences, the protein content decreased at the maximum concentration tested. The activity of the GR in the presence of different concentrations of PbAc 2 shows an increase in both parts of the analyzed plant being significant in the leaves (Figure 5A & 5B).…”
Section: Biochemical Characterization Of S Lycopersicum CV Amaliamentioning
confidence: 94%
“…In the treatments analyzed, no significant differences were found in the leaves in terms of total protein content, but in the stem the highest concentration (100 mg kg -1 ) was significantly higher than the control in 135.1% and that the treatment with 50 mg kg -1 of PbAc 2 (136.59%), causing a significant decrease in the variable analyzed in both treatments (0 and 50 mg kg -1 of PbAc 2 ) (Figure 4A & 4B). This increase in the content of total soluble proteins in the maximum concentration of PbAc 2 used could be due to a saturation in the mechanisms of retention of Pb in the stem, and consequently the finite capacity of this organ to act as a reservoir of the metal, 14 which continues to the leaves, where, although without significant differences, the protein content decreased at the maximum concentration tested. The activity of the GR in the presence of different concentrations of PbAc 2 shows an increase in both parts of the analyzed plant being significant in the leaves (Figure 5A & 5B).…”
Section: Biochemical Characterization Of S Lycopersicum CV Amaliamentioning
confidence: 94%
“…The second experiment was conducted in a factorial arrangement with three sunflower genotypes × two levels of lead (0 and 0.65 mM). This level of lead was based on recommendation of Abreu et al (2016), who indicated that sunflower tolerates Pb up to this level and the soil contamination with Pb usually does not exceed this limit. The genotypes were seeded in 200 mL plastic cups, using washed sand as substrate, and daily irrigated with distilled water.…”
Section: Experimental Conditions and Treatmentsmentioning
confidence: 99%
“…As the increase in these compounds was observed only in the roots of Pb-sensitive genotypes, the results suggest that the energy cost for osmoregulation through the synthesis of the organic compounds was higher in the H251 and AG963 genotypes than in the BRS-G27. Changes in the concentrations of carbohydrates and amino acids also evidence Pb-induced disturbances in cell metabolism (Abreu et al, 2016).…”
Section: Experiments 2: Physiological Nutritional and Biochemical Par...mentioning
confidence: 99%
See 2 more Smart Citations